Detection, characterization and possible biofragmentation of synthetic microfibers released from domestic laundering wastewater as an emerging source of marine pollution. (December 2022) - Mishra, Sunanda; Dash, Debasis; Das, Alok Prasad
Abstract: Synthetic microfibers are universally recognized as an emerging pollutant in all ecosystems. The present investigation focuses on the evaluation and quantification of synthetic microfiber released from domestic laundering wastewater from different regions of Bhubaneswar city of Odisha state of India. The estimated number of microfibers collected from 500 ml of sample varied from 200 to 500 in numbers with an average amount of biomass in the range of 0.4–4 g. The surface morphology of the samples was assessed by Scanning Electron Microscopic analysis which revealed that the fibers were having a length of approximately 10–30 mm and diameter of 10–20 μm. Carbonyl (CO) stretching band at 1711 cm −1 and Aldehyde (CH) Weak bond at 2917.38 cm −1 absorption were recorded from Fourier transform infrared spectroscopic analysis. As microfibers released from synthetic apparels are major source of environmental microplastic pollution their precise detection could help in controlling this problem. Highlights: This investigation identifies domestic laundering as a major source of synthetic microfiber pollution. Visual identification, Microscopic characterization and Spectroscopic analysis of Synthetic Microfibers were carried out. Possible mechanism of microfiber biofragmentation in aquatic ecosystem has been explained. Rigorous research and public awareness are highly essential to combat marine microfiber pollution.